2017
DOI: 10.1158/1055-9965.epi-16-0337
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in the Fecal Microbiota Associated with Adenomatous Polyps

Abstract: Background Adenomatous polyps are the most common precursor to colorectal cancer (CRC), the second leading cause of cancer death in the United States. We sought to learn more about early events of carcinogenesis by investigating shifts in the gut microbiota of patients with adenomas. Methods We analyzed 16S rRNA gene sequences from the fecal microbiota of patients with adenomas (n=233) and without (n=547). Results Multiple taxa were significantly more abundant in patients with adenomas, including Bilophila… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
150
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 165 publications
(158 citation statements)
references
References 79 publications
6
150
0
2
Order By: Relevance
“…As previous studies described, Desulfovibrio had the capacity to degrade sulfate and produce high levels of hydrogen sulfide, which is regarded as a genotoxic agent that might play a role in colitis and colonic tumorigenesis . Desulfovibrio also displays a flourish of relative abundance in IBD colon tissues and in patients with adenoma and rectal cancer . However, most studies have shown that the abundance of Desulfovibrio in the intestinal tract of colon cancer patients does not increase .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previous studies described, Desulfovibrio had the capacity to degrade sulfate and produce high levels of hydrogen sulfide, which is regarded as a genotoxic agent that might play a role in colitis and colonic tumorigenesis . Desulfovibrio also displays a flourish of relative abundance in IBD colon tissues and in patients with adenoma and rectal cancer . However, most studies have shown that the abundance of Desulfovibrio in the intestinal tract of colon cancer patients does not increase .…”
Section: Discussionmentioning
confidence: 99%
“…41 Desulfovibrio also displays a flourish of relative abundance in IBD colon tissues and in patients with adenoma and rectal cancer. 14,[42][43][44] However, most studies have shown that the abundance of Desulfovibrio in the intestinal tract of colon cancer patients does not increase. 45,46 Considering its role in triggering colonic inflammation, Desulfovibrio may be of larger significance in CAC initiation and progression than in sporadic colorectal cancer.…”
Section: Cxcl1mentioning
confidence: 99%
“…Stool DNA extraction [21], quantification, and amplification was performed as described previously [44]. Colon tissue was thawed, weighed, and homogenized prior to DNA extraction.…”
Section: Methodsmentioning
confidence: 99%
“…Butyrate, a short chain fatty acid (SCFA), is reportedly both an inducer [19] and an inhibitor [20] of CRC tumor development. Hydrogen sulfide, which has been implicated in our work and others’ [12,2123], is a genotoxic and cytotoxic agent at physiologic concentrations [13,24,25], but it has also been reported as an anti-inflammatory and potentially anti-tumor agent [2630]. …”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation